2011
DOI: 10.1128/aem.02130-10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a New Probiotic Saccharomyces cerevisiae Strain on Survival of Escherichia coli O157:H7 in a Dynamic Gastrointestinal Model

Abstract: Survival ofEscherichia coliO157:H7 was investigated using a dynamic gastrointestinal model. A high bacterial mortality was observed in the stomach and duodenum. In contrast, bacteria grew in the distal parts of the small intestine. The coadministration ofSaccharomyces cerevisiaeCNCM I-3856 led to a significant reduction of bacterial resumption, maybe through ethanol production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 32 publications
4
52
0
1
Order By: Relevance
“…Another significant number of yeast species, such as K. lactis, D. hansenii, T. delbrueckii and S. cerevisiae, have shown tolerance to traverse the gastrointestinal tract, inhibit the enteropathogens, adhere the intestinal CaCO 2 cell line and present an immunostimulatory activity [40][41][42]. In particular, S. cerevisiae has shown its ability to prevent the survival of E. coli O157:H7 under simulated gastrointestinal conditions by the production of ethanol [43]. Although research of olive yeast strains with the properties mentioned above is a promising task, it is important for olive yeasts to adhere on to the olive skin and survive during storage and/or packaging, in order to be ingested by consumers at elevated numbers.…”
Section: Functional Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another significant number of yeast species, such as K. lactis, D. hansenii, T. delbrueckii and S. cerevisiae, have shown tolerance to traverse the gastrointestinal tract, inhibit the enteropathogens, adhere the intestinal CaCO 2 cell line and present an immunostimulatory activity [40][41][42]. In particular, S. cerevisiae has shown its ability to prevent the survival of E. coli O157:H7 under simulated gastrointestinal conditions by the production of ethanol [43]. Although research of olive yeast strains with the properties mentioned above is a promising task, it is important for olive yeasts to adhere on to the olive skin and survive during storage and/or packaging, in order to be ingested by consumers at elevated numbers.…”
Section: Functional Propertiesmentioning
confidence: 99%
“…Despite the large amount of beneficial properties that these microorganisms could offer to the final product, recent findings showed that yeasts are not only in the cover brines, but also on the fruit epidermis, which indicates a promising source of probiotic strains [43,81]. The production of an innovative and functional food hav ing the advantages of probiotic yeasts, can contribute to a final product with added value, even higher than it already has.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…by food matrices [47][48][49] and age conditions [48]. In particular, thanks to the potential of the TIM model, Roussel et al [49] have shown that differences in digestive physicochemical parameters related to age conditions may partly explain the higher susceptibility of children (compared to adults) to EHEC infections and HUS.…”
Section: Bacterial Survival In the Human Digestive Tractmentioning
confidence: 99%
“…Other more recent studies have evaluated the survival of EHEC strains by using dynamic multicompartmental in vitro models that closely mimic the gastric, small intestinal, and colonic human digestive conditions. In the TNO GastroIntestinal model (TIM), which simulates the stomach and the three segments of the human small intestine, it has been shown that EHEC survival was affected in the stomach and duodenum (when ingested within a food matrix but not with a glass of water), while bacterial growth was observed at the end of digestion in the jejunum and ileum [47][48][49]. This growth renewal in the distal parts of the small intestine was probably linked to the occurrence of less stringent conditions, such as neutral pH and lower concentrations of bile salts due to their reabsorption (as occurred in vivo).…”
Section: Bacterial Survival In the Human Digestive Tractmentioning
confidence: 99%
“…However, some authors already reported that Saccharomyces cerevisiae significantly reduced E. coli O157:H7 growth in a dynamic multi-compartmental digestion system, possibly through a potential inhibitory role of ethanol produced by the yeast (149 Due to the low number of patients with mucositis and the variability of the microbiota among patients, we were not able to elucidate if mucositis was associated with specific changes in the microbiota that could promote MRE colonization. Taking into account a recent study reporting differences in the composition of the oral microbiota depending on the mucositis severity (154), it is likely that mucositis could also produce changes in the gut microbiota, which may impact MRE colonization levels.…”
Section: Microbiota Dysbiosis and Mre Colonization And Persistence Inmentioning
confidence: 81%